Categorization of English Varieties Used in Students’ Video Presentations - Ayu Indari; Afdhalina (Institute of Computer Science (IOCS), 2023)
The characteristic of Indonesian people especially students in the school or university are more contributing of English varieties. Video presentation is one of the phenomena occurring in English varieties. The aim of the study is to identify categorization of English varieties used in students’ video presentations. This study focuses: 1) how the categorization of English varieties used in students’ video presentations; 2) what the dominant categorization of English variety in students’ video presentations is; 3) why the dominant categorization of English variety used in students’ video presentations. This study will apply the qualitative method. The data is obtained from the students’ video presentations in STKIP Budidaya Binjai and Battuta University. The data will be conducted by applying content analysis. The stages of the study are: 1) collecting the data from the students’ video presentation in the group tasks; 2) categorization of English varieties into pronunciation, plural, and grammar; 3) identifying the dominant categorization of English varieties in students’ video presentation; 4) investigation the reason of the dominant categorization of English varieties in students’ video presentation. The results are: 1). the categorization of English varieties consists of pronunciation, plural, and grammar base on the data in spoken area, 2). the dominant of the categorization English varieties chosen is because the highest percentage used in the video. The percentage of pronunciation is 73.92%, 3).